Don’t underestimate the benefits of being misunderstood - Gibson, Edward; Tana, Caitlin; Futrella, Richard; Mahowalda, Kyle; Lars Konieczny; Barbara Hemforth; Fedorenko, Evelina (Psychological Science, 2017)
Being a non-native speaker of a language poses challenges. Individuals often feel embarrassed by the errors they make when talking in their second language (L2). However, here we report an advantage of being an L2 speaker: native speakers give foreign-accented speakers the benefit of the doubt when interpreting their utterances, such that apparently implausible utterances delivered in a foreign accent are more likely to be interpreted in a plausible way. Across three replicated experiments, we demonstrate that native English speakers are more likely to interpret implausible utterances such as “the mother gave the candle the daughter” as similar plausible utterances (“the mother gave the candle to the daughter”) when those utterances are produced with a foreign accent. This result follows from the general model of language interpretation in a noisy channel (Gibson et al., 2013), under the hypothesis that listeners assume a higher error rate in foreign-accented speech.